Social and Management Research Quantitative Analysis for Medium Sample: Comparing of Lisrel, Tetrad, GSCA, Amos, SmartPLS, WarpPLS, and SPSS - Agus Purwanto; Masduki Asbari; Teguh Iman Santoso; Vip Paramarta; Denok Sunarsi (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The purpose of this study is to compare the results of quantitative research data processing in the social field using Lisrel, Tetrad, GSCA, SPSS, SmartPLS, WarpPLS and Amos software. This research method is quantitative and research data analysis uses the four types of software to obtain a comparison of the results of the analysis. The analysis in this study focuses on the analysis of hypothesis testing and regression analysis. Regression analysis is used to measure how much influence the independent variable has on the dependent variable. The data from this study used quantitative data derived from questionnaire data totaling 122 respondents with four research variables, namely transformational leadership variables, leader member exchange, organizational citizenship behavior and performance. Based on the results of the analysis using SPSS, SmartPLS, WarpPLS and Amos software, it was found that there was no significant difference in the significance value of p-value and t-value. There is also no significant difference in the determination value, and the correlation value in the resulting structural equation also has no significant difference in results.